Genetic ancestry and population structure in the All of Us Research Program cohort - Shivam Sharma; Shashwat Deepali Nagar; Priscilla Pemu; Stephan Zuchner; SEEC Consortium; Leonardo Mariño-Ramírez; Robert Meller; I. King Jordan (Nature Communications)
Abstract We analyzed participant genomic variant data to characterize population structure and genetic ancestry for the All of Us cohort (n = 297,549). There is substantial population structure in the cohort, with clusters of closely related participants interspersed among less related individuals. Participants show diverse genetic ancestry, with major contributions from European (66.4%), African (19.5%), Asian (7.6%), and American (6.3%) continental ancestry components. Participant genetic similarity clusters show group-specific ancestry, with distinct patterns of continental and subcontinental ancestry among groups. African and American ancestry are enriched in the southeast and southwest regions of the country, respectively, whereas European ancestry is more evenly distributed across the US. The diversity of All of Us participants’ genetic ancestry is negatively correlated with age; younger participants show higher levels of genetic admixture compared to older participants. Our results underscore the ancestral genetic diversity of the All of Us cohort, a crucial prerequisite for genomic health equity.